QUALITY OF LIFE AND HEALTH SECURITY AMONG THE SLUM NEIGHBOURHOODS OF MIDNAPORE MUNICIPALITY, INDIA - Bikash Dutta; Utpal Roy; Manas Das; Sutapa Das; Sutapa Rath (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The concept of quality of life and health security is multidimensional and dynamically varies across places with respect to physical, socio-economic and psychological environments. Health security can improve quality of life, health status, life expectancy and adaptive capabilities as well as prevent disease progression. Slums are examples of the most vulnerable localized communities in the urban morphology that face a range of difficulties. This study aimed to examine the spatial distribution and correlation of and between the quality of life and health security among the slum neighbourhoods of Midnapore municipality as well as to find the similarity among the methods employed under study. The modified quality of life (QoLI) and health security index (HSI) was developed using inductive and deductive methods with the available datasets through a questionnaire survey. The results of the analysis show that slum neighbourhoods are more vulnerable with least prepared for their health security while living with decent to moderate quality of life. The ordinary least square (OLS) method was examined among the indicators of quality of life and health security showing a statistically significant correlation. This prototype study may help the researcher for further study at a local scale with the specific method whenever needed. Moreover, it is suggested to the local authority, policymakers, NGOs and district planning commission that more community participation, awareness creation and planning interventions can improve the place inequalities of the quality of life and health security among the slum neighbourhoods.